CORRELATION BETWEEN HEMATOCRITE AND HEMOGLOBIN COUNT WITH HOSPITALISAZION DURATION OF ACUTE DIARRHEAL CHILDREN PATIENTS IN UNDATA GENERAL HOSPITAL YEAR 2014 - Sari, Puspita; B.P, Herman (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2016)
Background: Diarrhea is one of major causes of morbidity and mortality in almost geographic regions of the world. All age groups can be infected with gastroenteritis. World Health Organization (WHO) reported that diarrhea  cause 3.5 millions deaths for one year in children under 5 years with  incidence of diarrhea is about 80%. Duration of hospitalization is a parameter commonly used to measure one episode of the hospitalization duration. In the Eradication Guidelines of Diarrhea 5th Edition, the former hospitalization target in acute diarrhea patients according to Department of Health Republic Indonesia is about 4 days or 96 hours.Methods: This study is an analytic observational, by using cross-sectional design and purposive sampling for data’s retrieval. Data’s retrieval using secondary data which was medical records of patients who are hospitalized due to acute diarrhea i Undata hospital Palu from 1 January to 31 December 2014, which includes hemoglobin, hematocrit count and duration of hospitalization. Data analyzing conducted with Chi Square test.Results: There were 97 samples of this research.  SPSS correlation test using chi-square test for hematocrit levels showed that there is no correlation between hematocrit count with hospitalization duration of acute diarrhea children patients. Based on the value of p> value of α is p = 0.097. Hemoglobin based on the test results measured by chi-square test showed that there is correlation between hemoglobin and hospitalization duration of patients with diarrhea. It is based on the value of p <α value ie, p = 0.003Conclusions: There was no correlation between hematocrit levels with hospitalization duration of acute diarrhea patients on children and there is correlation between hemoglobin levels and longer hospitalization duration of acute diarrhea children patients. Keywords: acute diarrhea, hospitalization duration, Hemoglobin, Hematocrit count.Latar Belakang: Diare  hingga saat ini masih merupakan salah satu penyebab utama kesakitan dan kematian hampir di seluruh daerah geografis di  dunia dan semua kelompok usia bisa terinfeksi gastroenteritis. World Health Orginazation (WHO) melaporkan bahwa dalam satu tahun diare dapat menyebabkan 3,5 juta kematian, dimana pada anak-anak dengan umur dibawah 5 tahun angka kejadian diare mencapai 80%. Lama rawat inap adalah istilah yang umum digunakan untuk mengukur durasi satu episode rawat inap. Dalam Pedoman Pemberantasan Diare Edisi ke 5, target lama rawat inap pasien Diare Akut menurut Depkes RI adalah 4 hari atau 96 jam.Metode Penelitian: Penelitian ini merupakan penelitian observasional analitik dengan desain penelitian cross-sectional. Teknik pengambilan data ialah purposive sampling. Pengumpulan data menggunakan data sekunder yaitu data rekam medis pasien Diare  Akut  yang dirawat inap di RSUD Undata Palu periode 01 Januari - 31 Desember 2014, yang mencakup Kadar  Hemoglobin, Kadar  Hematokrit   dan lama rawat inap. Analisis data menggunakan statistik uji Chi Square.Hasil Penelitian: Terdapat 97 sampel, Dari  hasil analisis data program komputer SPSS menggunakan uji korelasi  chi-square untuk  kadar  hematokrit  diperoleh  bahwa  tidak  ada  hubungan  antara  kadar  hematokrit  dengan  lama  rawat  inap  pasien diare  akut  pada  anak. Hal ini didasarkan pada nilai p > nilai α yaitu p = 0,097. Pada  Kadar  Hemoglobin  hasil analisis data program komputer SPSS menggunakan uji statistik chi-square maka diperoleh bahwa terdapat hubungan antara Kadar  Hemoglobin  dengan lama rawat inap pasien Diare. Hal ini didasarkan pada nilai p < nilai α yaitu p =0,003.Kesimpulan: Tidak terdapat hubungan antara  kadar hematokrit dengan lama  rawat  inap  pasien  diare  akut  pada  anak  dan  terdapat  hubungan  antara  kadar  hemoglobin  dan  lama  rawat  inap  pasien  diare  akut  pada  anak. Kata kunci: Diare  Akut, lama rawat inap, Kadar  Hemoglobin, Kadar Hematokrit.